A Study on Acceptance to Voluntarily Participate in Breast Milk Bank Activities amongst Antenatal and Postnatal Women in Three Hospitals of Bhopal - Veena Melwani; Soumitra Sethia; Madhav Bansal; Amreen Khan; Satish Melwani; Angelin Priya (Medsci Publications, 2018)
Background: Pasteurised Donor human milk (PDHM) is regarded as "the next best" after the biological mother's breast milk. The aim of the study was to assess the awareness about breast milk banking among antenatal and postnatal women and their willingness   to donate their breast milk to the bank or accept it from the bank. Materials & Methods: A cross sectional study was carried out on 350 Antenatal and Postnatal women from 3 hospitals of Bhopal. Purposive sampling was used and 104 antenatal women (>8 months gestation) and 246 postnatal women (<6 weeks) were en- rolled. The study was conducted from 1 September to 30 Novem- ber 2016. The data was collected using pre-designed semi struc- tured questionnaire. Results: Out of 246 postnatal women who were interviewed, 86.6% women were currently breastfeeding their child. Knowl- edge regarding importance of colostrums and meaning of exclu- sive breastfeeding was present in 73.4% and 85% participants re- spectively. The knowledge about existence of breast milk bank was 10% while willingness to accept the milk was 85.4% and to donate was 84.9% in study participants. Conclusion: The knowledge about existence of breast milk bank in study participants was found to be very less. Lack of awareness about existence of breast milk banks was perceived as major bar- rier in utilisation of breast milk bank services.